Nutritional significance of velvet bean (Mucuna pruriens) and opportunities for its processing into value-added products - D. Sowdhanya; Jyoti Singh; Prasad Rasane; Sawinder Kaur; Jaspreet Kaur; Sezai Ercisli; Hitesh Verma (Journal of Agriculture and Food Research, 2024)
Underutilized legume comprises vital nutrients with a higher proportion of protein (23-43 %) equal to soybean, and lima bean and greater than chickpea and green pea. In addition, it has a good calorific value, carbohydrates, vitamins, and minerals. The presence of bioactive components such as polyphenols and flavonoids increases the market demand in pharmacological industries at the global level. It exhibits several pharmacological properties like antioxidant, anti-inflammatory, anti-diabetic, antimicrobial, and antihypertensive. It has a higher concentration of antinutritional compounds like l-DOPA, phytates, tannin, oxalate, hydrogen cyanide, and trypsin inhibitors. These barriers prevent the consumption of velvet beans, and they can be reduced by both conventional and modern methods. The methods include dehulling, boiling, soaking, cooking, roasting, toasting, fermentation, sonication, and acid and alkali treatment. Each method has a distinct effect on the method of removal of antinutrients and it has an impact on its reduction percentage. The degree of modification in the physicochemical composition does fall under a considerable limit and doesn't affect the actual nutritional composition of the mucuna seeds. It is considered an alternative protein source to animal protein, hence extraction of protein from velvet beans has a better scope to isolate and concentrate protein and its peptides. This flour has been utilized in food formulations like bread, crackers, food mix, beverage mix, mucuna milk, and traditional foods like moin moin, chapatti, and mash. The major constraint of the utilization in the food industry is due to the presence of antinutrients and their removal and depletion by various treatments was focussed. It can replace the source of animal protein, fulfill the protein insufficiency of the population and increase food security.